PENGARUH UPAH MINIMUM DAN TINGKAT PENGANGGURAN TERHADAP JUMLAH PENDUDUK MISKIN DI KABUPATEN KOTA PROVINSI KALIMANTAN BARAT - admin, FAIZAL MAULANA B01109068 (Jurnal Pembangunan dan Pemerataan, 2018)
Development is a process that aims to achieve social prosperity through economic development. Benchmark for the success of development can be seen from the economic growth, economic structure and the level of inequality between people, between regions and between sectors . The number of poor people is a complex issue that is influenced by a variety of interrelated factors, such as income levels, unemployment, health, education, access to goods and services, location, geography, and the environment . The number of poor people is the inability to meet basic needs such as food, shelter, and health .This study aims to determine the effect of the minimum wage and the unemployment rate to the number of poor in the District Municipality of West Kalimantan Province . This research using quantitative descriptive method using panel data (combination of time series data and cross section data ) that uses multiple regression analysis method.The results of this study indicate that the minimum wage society positive and significant effect on the number of poor people. Because most of the population works in the informal sector Indonesia . While the unemployment rate is negative and significant effect on the number of poor people, because the informal sector is included in unemployment.Keywords : Minimum Wages , Unemployment Rate and Number of Poor People in City District of West Kalimantan Province